Protection of historical cultural heritage against dangers resulting from terrorist activity (Part I) - Chrzczonowicz, Piotr (Studia Iuridica Toruniensia, 2017)
Either in information transmitted by mass media or discussions concerning phenomenon of terrorism which take place in many countries (including Poland), in the mainstream of reMections on the activity of organized terrorist groups or so-called ‘lone-wolf’ terrorists, there aren’t exposed expressively dangers to cultural heritage, including historical monuments. But cases in which exceptionally valuable historical heritage goods are intentionally and cynically annihilated in military conflicts or in consequence of terrorism acts were in the past, they exist nowadays and, unfortunately, they will be appearing in the future. As far as in military conflicts – in the meaning present in public international law – there is a hope that such conMicts are civilized and their subjects respect diUerent international law regulations and customs, such hope in case of fanatic, incalculable and unpredictable terrorist activity is rather vain. It’s worthy to look at solutions concerning protection of cultural heritage goods and counteraction of terrorism, to get to know better the quality and efectiveness of mechanisms created in order to protect historical cultural heritage in the context of challenge which is contemporary terrorism. The paper is divided into two parts. In the Wrst one there is contained the characteristics of contemporary confrontation of states with terrorism in the context of dangers stemming from this phenomenon and threatening to historical cultural goods. In this part of paper there are presented, among others, instruments of public international law as well as European Union law which could be applied in the mentioned confrontation. The second part of the paper contains considerations relating to motivational basis for terrorist acts against historical cultural goods and their consequences, efectiveness of legal solutions protecting cultural heritage and practical actions of state agencies responsible for ensuring safety and public order as well as other subjects having duty to care for cultural heritage (including historical monuments) and responsible for preservation of this heritage for next generations.